Review on invasive and semi-invasive procedures to treat abnormal uterine bleeding in Iranian traditional medicine - Alireza yargholi; Mohammad Ali Zareian; Sousan Hafizi; Roghaye Faryabi; Maliheh Tabarraei (Mashhad University of Medical Sciences, 2017)
Introduction: Abnormal uterine bleeding is the most common reason for referring to the physician in women of reproductive age. In conventional medicine, based on the severity and cause of bleeding, variety of systemic or local medical and surgical treatments is suggested. In Iranian traditional medicine, for the treatment of uterine bleeding, in addition to food and medical advice, semi-invasive and invasive procedures are also considered. This review study was performed with aim to extract and evaluate semi-invasive and invasive procedures which are used in common texts of Iranian traditional medicine for the treatment of uterine bleeding. Methods: In this review and library study, English and Persian articles related to the details of the proposed invasive or semi-invasive procedures for treatment of uterine bleeding were searched from databases of Google scholar, Pubmed, Scopus and SID and using the keywords of management, menorrhagia, Abnormal uterine bleeding , and Efrat-e Tams  and also the combination of these two words without time limitation. At the end, data was analyzed by content analysis method. Results: In searching of different sources of semi-invasive and invasive procedures for treatment of abnormal uterine bleeding including: phlebotomy, dry cupping, wet cupping, limbs tying, breasts tying, vaginal douching, vomiting, sitzbath, there is still limited evidence regarding the effects of these therapies and further studies are needed. Conclusion: In traditional medicine, variety of semi-invasive and invasive procedures is suggested for treatment of abnormal uterine bleeding that according to the lack of enough clinical trials, the efficacy and complications of these methods cannot be compared with surgery. But, we can do further research and clinical trials to prove or disprove the effectiveness of these procedures and help to reduce the complications of pelvic surgeries.